2020
DOI: 10.1002/pld3.286
|View full text |Cite|
|
Sign up to set email alerts
|

Diurnal metabolic regulation of isoflavones and soyasaponins in soybean roots

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…In this study, they confirmed the positive regulation of GmMYB29A2 that leads to the increased conversion of isoflavonoids into the glyceollin and thus develops resistance against Phytophthora sojae (Jahan et al, 2020). Matsuda et al (2020) studied the diurnal metabolic regulation of isoflavones and soy saponins in soybean roots. The transcriptome and metabolite analysis of soybean plants at 6-h intervals for 48 h in a 12-h light-12-h dark condition.…”
Section: Regulation Of Isoflavone Production Through Genetic Engineering In Soybeansupporting
confidence: 64%
See 1 more Smart Citation
“…In this study, they confirmed the positive regulation of GmMYB29A2 that leads to the increased conversion of isoflavonoids into the glyceollin and thus develops resistance against Phytophthora sojae (Jahan et al, 2020). Matsuda et al (2020) studied the diurnal metabolic regulation of isoflavones and soy saponins in soybean roots. The transcriptome and metabolite analysis of soybean plants at 6-h intervals for 48 h in a 12-h light-12-h dark condition.…”
Section: Regulation Of Isoflavone Production Through Genetic Engineering In Soybeansupporting
confidence: 64%
“…In the root tissues, isoflavone and soy saponin biosynthetic genes showed opposite patterns; the former are highly expressed in the day, whereas the latter are strongly triggered at night. GmMYB176 , which encodes an isoflavone biosynthesis transcription factor, was upregulated from ZT0 (6:00 A.M. ) to ZT6 (12:00 A.M. ), accompanied by the stimulation of isoflavone biosynthetic genes at ZT6 ( Matsuda et al, 2020 ). Recently, Vadivel et al (2021) have found that the RNAi silencing of transcription factor GmbZIP5 reduced the isoflavone accumulation in hairy roots.…”
Section: Regulation Of Isoflavone Production Through Genetic Engineering In Soybeanmentioning
confidence: 99%
“…Regarding composition, soybean root exudates (Figure B) primarily comprise group A soyasaponins followed by group B soyasaponins, whereas DDMP soyasaponins remain undetected and presumably absent from root exudates . However, soybean root exudates characterized by another study report that group A soyasaponin (Ab) content was moderately higher than that of group B soyasaponin (Bb) content . General trends observed in root exudates contrast to soyasaponin composition found in soybean leaf and root tissues where DDMP soyasaponins are the primary components.…”
Section: Root Exudates and Plant-benefiting Microbes In The Rhizospherementioning
confidence: 91%
“…The combined supernatant from each sample was dried under a nitrogen stream at 50°C and redissolved in 150 μl methanol. Isoflavones were analyzed by LC-MS/MS as described [20].…”
mentioning
confidence: 99%
“…While the secretion from whole roots was analyzed in the hydroponic culture media, the secretion from the field-grown soybean was analyzed using a 3 cm root-tip section. The A Self-archived copy in Kyoto University Research Information Repository https://repository.kulib.kyoto-u.ac.jp possibility that partial soil removal induced the isoflavone biosynthesis and increased the isoflavone levels within 2 h is probably small because it is suggested to take more than 3 h for the roots to accumulate isoflavones after gene induction in Arabidopsis thaliana and soybean [20,21]. The difference in the magnitude of secretion is, therefore, presumably attributable to environmental conditions, i.e., sterile hydroponics vs. non-sterile field environments.…”
mentioning
confidence: 99%